Electrochemical oxidation of propanil and related N-substituted amides - Garrido, E. Manuela (2013)
The electrochemical behaviour of propanil and related N-substituted amides (acetanilide and N,N-diphenylacetamide) was studied by cyclic and square wave voltammetry using a glassy carbon electrode. Propanil has been found to have chemical stability under the established analytical conditions and showed an oxidation peak at +1.27V versus Ag/AgCl at pH 7.5. N,N-diphenylacetamide has a higher oxidation potential than the other compounds of +1.49V versus Ag/AgCl. Acetanilide oxidation occurred at a potential similar to that of propanil, +1.24V versus Ag/AgCl. These results are in agreement with the substitution pattern of the nitrogen atom of the amide. A degradation product of propanil, 3,4-dichloroaniline (DCA), was also studied, and showed an oxidation peak at +0.66V versus Ag/AgCl. A simple and specific quantitative electroanalytical method is described for the analysis of propanil in commercial products that contain propanil as the active ingredient, used in the treatment of rice crops in Portugal.